Acid‐in‐Clay Electrolyte for Wide‐Temperature‐Range and Long‐Cycle Proton Batteries. Issue 23 (2nd May 2022) - Wang, Shitong; Jiang, Heng; Dong, Yanhao; Clarkson, David; Zhu, He; Settens, Charles M.; Ren, Yang; Nguyen, Thanh; Han, Fei; Fan, Weiwei; Kim, So Yeon; Zhang, Jianan; et al.
Abstract: Proton conduction underlies many important electrochemical technologies. A family of new proton electrolytes is reported: acid‐in‐clay electrolyte (AiCE) prepared by integrating fast proton carriers in a natural phyllosilicate clay network, which can be made into thin‐film (tens of micrometers) fluid‐impervious membranes. The chosen example systems (sepiolite–phosphoric acid) rank top among the solid proton conductors in terms of proton conductivities (15 mS cm −1 at 25 °C, 0.023 mS cm −1 at −82 °C), electrochemical stability window (3.35 V), and reduced chemical reactivity. A proton battery is assembled using AiCE as the solid electrolyte membrane. Benefitting from the wider electrochemical stability window, reduced corrosivity, and excellent ionic selectivity of AiCE, the two main problems (gassing and cyclability) of proton batteries are successfully solved. This work draws attention to the element cross‐over problem in proton batteries and the generic "acid‐in‐clay" solid electrolyte approach with superfast proton transport, outstanding selectivity, and improved stability for room‐ to cryogenic‐temperature protonic applications. Abstract : An acid‐in‐clay electrolyte is prepared by integrating fast proton carriers in a natural phyllosilicate clay network, ranking top among the solid proton conductors in terms of high proton conductivities, enlarged electrochemical stability window, and reduced chemical reactivity. Benefitting from the above advantages, the acid‐in‐clay electrolyte can solve two main challenges in proton batteries: gassing and poor cycling performance.